2001
DOI: 10.1152/ajpcell.2001.281.1.c350
|View full text |Cite
|
Sign up to set email alerts
|

Ionomycin causes activation of p38 and p42/44 mitogen-activated protein kinases in human neutrophils

Abstract: Many receptor-linked agents that prime or activate the NADPH oxidase in polymorphonuclear neutrophils (PMNs) elicit changes in cytosolic Ca2+ concentration and activate mitogen-activated protein (MAP) kinases. To investigate the role of Ca2+ in the activation of p38 and p42/44 MAP kinases, we examined the effects of the Ca2+-selective ionophore ionomycin on priming and activation of the PMN oxidase. Ionomycin caused a rapid rise in cytosolic Ca2+ that was due to both a release of cytosolic Ca2+ stores and Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…This type of Ca 2+ -dependent activation of p38-MAPK has been reported in a number of cell types (Blanquet, 2000;Dehez et al, 2001;Elzi et al, 2001;Kreideweiss et al, 1999;Shigemoto-Mogami et al, 2001), including peripheral macrophages which express functional P2X4 receptor (Brone et al, 2007;Qureshi et al, 2007;Ulmann et al, 2010). In macrophages, P2X4 receptor activation of p38 MAPK is upstream from the production and release of prostaglandin E2 (Ulmann et al, 2010), a principal substrate for inflammation that sensitizes peripheral nociceptors (Portanova et al, 1996;Samad et al, 2002).…”
Section: Role Of Microglial P2x4 Receptors In Neuropathic Painmentioning
confidence: 76%
“…This type of Ca 2+ -dependent activation of p38-MAPK has been reported in a number of cell types (Blanquet, 2000;Dehez et al, 2001;Elzi et al, 2001;Kreideweiss et al, 1999;Shigemoto-Mogami et al, 2001), including peripheral macrophages which express functional P2X4 receptor (Brone et al, 2007;Qureshi et al, 2007;Ulmann et al, 2010). In macrophages, P2X4 receptor activation of p38 MAPK is upstream from the production and release of prostaglandin E2 (Ulmann et al, 2010), a principal substrate for inflammation that sensitizes peripheral nociceptors (Portanova et al, 1996;Samad et al, 2002).…”
Section: Role Of Microglial P2x4 Receptors In Neuropathic Painmentioning
confidence: 76%
“…This finding implies that activation of p38-MAPK by ATP is necessary for the release of BDNF from the pre-existing pool, and together with the Ca 2ϩ dependence of the early phase release, a mechanistically simple explanation is that Ca 2ϩ induces activation of p38-MAPK, which in turn stimulates BDNF release. Ca 2ϩ -dependent activation of p38-MAPK has been demonstrated in a number of cell types (Blanquet, 2000;Dehez et al, 2001) including immune cells (Kreideweiss et al, 1999;Elzi et al, 2001;Shigemoto-Mogami et al, 2001). There is, however, no evidence in the literature for involvement of p38-MAPK in the process of release of peptides from cells, and therefore, an alternative possibility is that activation of p38-MAPK is permissive for Ca 2ϩ -dependent BDNF release.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that Ca 2ϩ influx activates p38 MAPK and Erk1/2 in human neutrophils or PC12 cells. 35,36 Recently, it was reported that Y568 of human KIT (corresponding to murine Y567) is important of SFK activation and Shc phosphorylation resulting in Ras/Erk2 activation, 37 and p38 MAPK was involved in SCF-mediated cell migration. 22 In this report, for the first time, we showed that not only p38 MAPK but also Erk1/2 was involved in SCF-mediated cell migration, and that both MAPKs differentially transduce the signaling from Y567-induced SFK activation to Ca 2ϩ influx and cell migration.…”
Section: Discussionmentioning
confidence: 99%